Exploring Metaverse Integration in Education: A Case Study on Vocational School Teachers - Samsul Pahmi; Anggy Pradiftha Junfithrana; Edi Supriyadi (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2023)
The metaverse, gaining attention especially in education, holds the potential to transform traditional teaching methods and improve educational outcomes by creating immersive learning environments. This study, focusing on integrating the metaverse into mathematics education at SMK Hasina in Sukabumi, Indonesia, reveals insights through a qualitative case study. Educators showed varied understanding levels influenced by interest and technological backgrounds. Acknowledging the metaverse's potential, educators affirm its ability to enhance interaction and accessibility in education. Recommendations propose extensive educator training and integration methods for the metaverse, emphasizing its promise in engaging students and reshaping teaching methodologies for diverse learning styles. While it promises dynamic learning experiences and global collaborations, comprehensive research is needed to understand its full potential and challenges. Educator education and broader involvement are vital for effective integration into educational settings, enhancing outcomes and inclusivity in learning.